Формирование слоговой структуры слова у дошкольников с общим недоразвитием речи - Tikhonova N. V. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2022)
This article discusses the views of different authors on the problems of the formation of the syllabic structure of a word in preschool children with general underdevelopment of speech, as well as approaches and methods for correcting the syllabic structure in this category of children.
Keywords: общее недоразвитие речи; general underdevelopment of speech; слоговая структура слова; syllabic structure of the word